Exploring The Traditional Maritime Technology: Classification of Terengganu's Sea and River Perahu - Ngah, Nor Syamaliah; Ngah, NOR SURAYA AINI Nor Suraya Aini; Tengku Mohd, Tengku Azman; Ngah, Che Muhammad Azmi; Awang, Inche Mokhtar; Abdullah , Mohd Yusof; Hasan , Ramly (Journal of Human Capital Development (JHCD), 2025)
Terengganu's rich maritime history has led to the development of various watercraft designs, with local researchers extensively studying the history, types, and decoration of traditional boats, known as perahu. However, the classification of perahu based on their specific usage remains underexplored. Given the scarcity of written records on Terengganu's traditional perahu, this study combines interviews and observations to gather essential data. In line with the Sustainable Development Goal (SDG) 11, the research encourages collaboration between government and private entities, such as the Ministry of Higher Education, Universiti Teknologi Mara Seremban, Politeknik Ungku Omar, Terengganu State Museum, and the Royal Terengganu Institute for Historical and Legal Studies, aligning with SDG 17. The study aims to contribute to existing research by focusing on the classification of Terengganu's traditional perahu according to their specific river and sea applications. Adopting a case study approach, the research observes 15 traditional perahu and one prototype housed at the Terengganu State Museum, while one type is only represented through verbal accounts and is excluded. Interviews with experienced boatbuilders in Kuala Terengganu provide additional insights into the features of river and sea perahu. The study finds that, of the 16 types of perahu examined, five were designed for river navigation, while 11 were intended for the sea. The data were presented to the Maritime Unit at the Terengganu State Museum for validation. The variety of perahu in Terengganu is largely influenced by the region's geography, featuring both rivers and vast coastlines. These findings open avenues for further research into the evolution of Terengganu's traditional perahu.